Remote, elitist, or non-existent? - Garcia-Blanco, Inaki (Javnost (Ljubljana), 2013)
This paper looks at how British political elites discuss the European public sphere and citizens' participation within it. Drawing on 41 in-depth interviews with political elites - including politicians at national and European levels, journalists, political activists, and think-tank professionals - the paper explores interviewees' understandings of the European public sphere, and their perceptions about its vitality. Our research reveals a great deal of scepticism about the idea of a European public sphere, in part rooted in conventional British Euro-sceptic approaches, and in part fostered by a perception of the remoteness and democratic deficit of the European Union.
Keywords: Velika Britanija; politična elita; javnost; javna sfera; participacija